Improvement of the Method of Extended Removal of Lymph Nodes in the Treatment of Neoplasms in the Oropharynx (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This scientific article discusses the issue of improving the methods of extended lymph dissection in the treatment of oropharyngeal tumors, which are a significant problem in modern oncology. The main focus is on analyzing the clinical results of this procedure, including evaluating the effectiveness of improving long-term outcomes for patients, as well as studying the degree of reduction in the risk of tumor recurrence after surgery. The study is based on a comparative analysis of data obtained from patients who underwent extended lymph node dissection, compared with patients who received traditional methods of treatment. Emphasis is placed on the need to integrate this surgical intervention into a comprehensive approach to the treatment of oropharyngeal cancer, given its potential benefits in improving the quality of life of patients and reducing the likelihood of relapse. The article also examines the side effects and complications associated with extended lymph node dissection, analyzing their impact on the general condition and rehabilitation after surgery of patients. To sum up, the study suggests further directions for studying this technique, including developing criteria for optimal patient selection and risk minimization, as well as exploring the possibility of integrating with other treatments to achieve the best clinical results.